Zur Anwendung des Schienenbonus bei der Beurteilung von Verkehrsgeräuschen. - Möhler, Ulrich; Liepert, Manfred; Schreckenberg, Dirk (Springer-VDI-Verl., 2010)
In einer Literaturauswertung wurde untersucht, ob die Besserstellung der Bahn im Vergleich zu anderen Verkehrsträgern noch gerechtfertigt ist und somit der in zahlreichen Verordnungen verankerte Schienenbonus einer Überprüfung bedarf. Die Sichtung der Literatur lässt folgende Schlussfolgerungen zu: Die Festlegung des Schienenbonus im Rahmen der Verkehrslärmschutzverordnung erfolgte auf der Grundlage von Studien aus den Jahren 1978 und 1983 und wurde durch Studien aus dem Jahr 2001 weitgehend bestätigt. Die Ergebnisse decken einen umfangreichen akustischen Pegelbereich und sozialwissenschaftlichen repräsentativen Bevölkerungsquerschnitt ab. Durch die - politische - Setzung eines Schienenbonus auf 5 dB(A) wurde auf eine Differenzierung zugunsten einer einfachen Handhabung in der Praxis verzichtet. Ein Schienenbonus wurde auch in anderen europäischen Ländern aufgrund dortiger Untersuchungen eingeführt. Forschungsdefizite im Hinblick auf den Schienenbonus wurden vor allem hinsichtlich der Bewertung des Nachtschlafs, der tageszeitlichen Veränderungen in der Belästigung insbesondere abends sowie in besonderen akustischen Situationen (erhöhter Güterzuganteil, Hochgeschwindigkeitsstrecken) festgestellt. Die Untersuchungsergebnisse deuten darauf hin, dass aufgrund der inzwischen eingetretenen Veränderungen in der Verkehrszusammensetzung und im Freizeitverhalten der Bevölkerung eine Differenzierung in der Anwendung des Schienenbonus vorgenommen werden muss.

The survey examines the question, whether the advantage for the railway in comparison to other traffic noise sources is still justified. The survey shows, whether the numerous regulations regarding railway track bonuses need a new review and inspection. It is based on a literature analysis, which leads to following conclusions: The definition of the railway bonus according to german traffic noise law was based on the results of extensive sociological surveys from 1978 to 1983. These results were in the main confirmed by studies from 2001. The examinations covered an extensive acoustic level range and a representative sociological public profile. Due to the political setting, a railway-bonus of 5 dB(A) was established even though with regard to the scientific results, a possible differentiation was proposed. Regarding further research in different countries, a railway-bonus was also established in other European countries, such as Austria, Switzerland, France and the Netherlands. As an aspect, laboratory studies relating to sleeping disorders were carried out with the results that at same pass by sound level the measured sleep disturbances due to railway noise are higher than those from road traffic noise as well as air traffic noise. However the presented sound scenarios of railway noise were not realistic. Therefore the transfer of these results in a regulation with respect to the railway bonus seems not to be recommendable. Deficits in research were mainly detected regarding the assessment of sleep, changes in the noise annoyance during the day, especially in the evening, special acoustic situations e.g. increased freight traffic or high speed lines. The survey results lead us to the conclusion that the meanwhile current changes in traffic and leisure attitude of the general public, must indicate a new differentiation in railway bonus.
The application of the "railway -bonus" with regard to rating of traffic noise
Keywords: Umweltschutz; Lärmschutz; Verkehrslärm; Lärmpegel; Schienenverkehr; Eisenbahn; Lärmbelastung; Lärmschutzverordnung; Verkehrslärmschutzgesetz; Literaturauswertung